“Constant Stress Has Become the New Normal”: Stress and Anxiety Inequalities Among U.S. College Students in the Time of COVID-19 - Hoyt, Lindsay Till; Cohen, Alison K.; Dull, Brandon; Maker Castro, Elena; Yazdani, Neshat (Journal of adolescent health, 2021)
The purpose of this study is to document young adults' perceived stress and anxiety in a diverse sample of college students across the U.S. during the COVID-19 pandemic. We recruited, via Instagram, a sample of full-time college students aged 18–22 from across the U.S. We surveyed them in April (baseline; N = 707; mean age = 20.0, SD = 1.3) and July (follow-up) 2020. This study presents overall levels of perceived stress and general anxiety symptoms and inequalities across each of these outcomes by gender, sexual orientation, race/ethnicity, and household income. We also explore potential explanations for these health issues by analyzing baseline qualitative data. All students, on average, were suffering from perceived stress and anxiety, with especially high levels in April. We also identified inequalities in college student mental well-being, particularly by gender identity and sexual orientation. Women reported worse well-being compared with men; transgender and gender diverse and sexual minority youths reported worse outcomes than their cisgender, heterosexual peers at both time points. Qualitative data illustrate how the COVID-19 pandemic has generated educational, economic, and environmental stressors that are affecting college students' well-being. As colleges and universities think about how to manage and mitigate the infectious disease dimensions of COVID-19 among their student populations, they must also consider who is most at risk for increased stress and anxiety during the pandemic.